Pharmacists healthcare leadership forum 2025 - Hishamuddin, Muhammad Danish Aliff; Sugiman, Muhammad Hakim (Faculty of Pharmacy, 2025)
Pharmacists Healthcare Leadership Forum 2025 was a two-day event organised by the Malaysian Pharmacists Society – Hospital and Clinical Pharmacy Chapter. The event was held on 17th and 18th May 2025 at Taylor’s University Lakeside Campus. It was attended by two students, namely Muhammad Danish Aliff Bin Hishamuddin and Muhammad Hakim Bin Sugiman. The forum gathered pharmacists from across Malaysia to hear from notable pharmacy leaders who spoke on topics such as leadership in pharmacy, the evolving role of pharmacists in the digital era of healthcare, and entrepreneurial opportunities within the profession.